Cytokine, Sickness Behavior, and Depression - Dantzer, Robert (2009)
Sufficient evidence is now available to accept the concept that the brain recognizes cytokines as molecular signals of sickness. Clarifying the way the brain processes information generated by the innate immune system is accompanied by a progressive elucidation of the cellular and molecular components of the intricate system that mediates cytokine-induced sickness behavior. We are still far, however, from understanding the whole. Among the hundreds of genes that proinflammatory cytokines can induce in their cellular targets, only a handful has been examined functionally. In addition, a dynamic view of the cellular interactions that occur at the brain sites of cytokine production and action is missing, together with a clarification of the mechanisms that favor the transition toward pathology.